2011
DOI: 10.1136/annrheumdis-2011-200402
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cancer in a nationwide population cohort of 7852 patients with primary Sjögren's syndrome in Taiwan

Abstract: Patients with pSS, overall, did not have higher risk of cancer, and only patients aged 25-44 years were at an increased risk of cancer compared with their counterparts in the general population. Cancer screening for patients with pSS, especially female patients, should focus on NHL and multiple myeloma and thyroid gland cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 33 publications
7
76
3
3
Order By: Relevance
“…Some studies examined the association between pSS and overall malignancy risk but no consistent conclusion was drawn 3 11 13 14 16–18 22. The present meta-analysis with more strong evidence confirmed that pSS is closely associated with an increased overall risk of malignancy.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Some studies examined the association between pSS and overall malignancy risk but no consistent conclusion was drawn 3 11 13 14 16–18 22. The present meta-analysis with more strong evidence confirmed that pSS is closely associated with an increased overall risk of malignancy.…”
Section: Discussionmentioning
confidence: 45%
“…The result indicated that pSS was associated with a 53% increased risk for overall malignancy (table 2). The Galbraith plot showed that three studies might be major sources of heterogeneity (figure 2), two of which were conducted in Asia18 22 and one in Europe 16. Subgroup analysis showed that there was significant heterogeneity between the two studies in Asia but no heterogeneity in Europe (table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a female gender effect should be taken into account considering that the only one study that investigated the risk of NHL in male patients with pSS found no association. [53]. Secondly, studies in non-European countries are few and included small number of patients.…”
Section: Rtx Treatment In Pss-associated B-cell Lymphomamentioning
confidence: 98%
“…Although many studies have focused on the risk of neoplasia in SS [10][11][12][13][14], we found only four publications in which acute leukaemia was cited ( Table 1) [15][16][17][18]. The first publication reported on a 59-year-old woman with primary SS diagnosed in 1963.…”
Section: Literature Reviewmentioning
confidence: 99%